Associations between neighbourhood characteristics and participation in a population-based organised prostate cancer testing (OPT) programme: A register-based study of 50-year-old men - Emil Järbur; Rebecka Arnsrud Godtman; Carl Bonander; Ulf Strömberg; Ola Bratt (PLoS ONE, 2025)
Objectives Regional, population-based organised prostate cancer testing (OPT) began in Sweden in 2020. We investigated associations between participation and neighbourhood characteristics. Setting Region Västra Götaland’s OPT programme Methods Data were retrieved from the regional OPT database, for all 50-year-old men invited in 2020–2021. Addresses were linked to demographic statistical areas defined and socioeconomically described by Statistics Sweden. Logistic regression models were used to analyse participation based on neighbourhood deprivation, income, education, proportion of non-western immigrants, and degree of urbanisation, categorised in quintiles. Results are reported as unadjusted and adjusted odds ratios (ORs) with confidence intervals (CIs). Results Unadjusted participation was significantly lower in the quintiles of neighbourhoods with the highest deprivation index (OR 0.61, 95% CI 0.56–0.67), lowest income (OR 0.64, 95% CI 0.59–0.71), lowest education (OR 0.81, 95% CI 0.74–0.89), and highest proportion of non-Western immigrants (OR 0.70, 95% CI 0.64–0.77), compared with the opposite quintile. After adjustment for the other variables, significant gradients remained for deprivation (OR 0.65, 95% CI 0.57–0.74), proportion of non-Western immigrants (OR 0.78, 95% CI 0.69–0.88), and degree of urbanization (OR 0.78, 95% CI 0.71–0.87 for rural versus urban areas). No adjusted analysis was done for income owing to its strong correlation with deprivation. Conclusion Socioeconomic factors and degree of urbanisation influence participation in organised screening for prostate cancer. Actively inviting men for screening, does not in itself avoid socioeconomic disparity in early detection of prostate cancer.